Nutrition Education in Secondary Education (7th to 11th grades) Through the Crosscutting Topic "Education for Health" From an Useful-For-Life Approach - José Francisco Quirós-Rojas; María Isabel Torres-Salas; Narcy Villalobos-Sand (Universidad Nacional, Costa Rica, 2015)
This paper provides the results of a research study conducted to determine how science teachers from four schools of the San José Regional Branch of the Costa Rican Ministry of Public Education undertake the nutrition topic at their schools; and, at the same time, find out about their interest in approaching nutrition as an useful-for-life issue, through the crosscutting topic "Education for Health." In addition, this study intended to identify the perceptions of students about good nutrition in favor of healthy a lifestyle. Based on the nature of the work, the study followed a naturalistic paradigm towards a dominant qualitative approach, in a community-based type of study.  Questionnaires and interviews were used as research instruments; the sample included 6 science teachers and 60 students of ninth grade.   The information was analyzed and triangulated. The results indicated that teachers apply the useful-for-life approach in nutrition education, empirically; innovative activities are not widely used; and there is a need to strengthen knowledge regarding the use of crosscutting topics in the curriculum. In addition, this study reported that students are aware of-but do not implement-good daily life actions to change bad eating habits and favor preventive health.  This research project puts forward teaching strategies to be applied in secondary education (7th to 11th grades) to approach nutrition from this perspective.